Disparity in Sentencing and the Effectiveness of Indonesia's Narcotics Law: A Critical Analysis of Law No. 35 of 2009 - Alex Rikardo Siahaan; Hasan Hiawatha Rifai; Asmak Ul Hosnah (Arkus, 2025)
Drug abuse in Indonesia remains a pervasive issue with significant social, economic, and health implications. Law No. 35 of 2009 concerning Narcotics was enacted to combat this problem through comprehensive provisions encompassing prevention, criminalization, and rehabilitation. This study critically analyzes the implementation of Law No. 35 of 2009, focusing on sentencing disparities and their impact on achieving the law's objectives. This study employed a qualitative approach with a normative legal analysis. Primary data sources included Law No. 35 of 2009, related regulations, court decisions, and legal documents. Secondary data comprised academic publications, reports from government and non-government organizations, and expert opinions. Data analysis involved a comprehensive review and thematic analysis of the collected materials, focusing on identifying patterns, inconsistencies, and challenges in the application of the law. The study revealed a significant disparity in sentencing under Law No. 35 of 2009. Drug users, often suffering from addiction, frequently receive harsher punishments than drug dealers, who play a more significant role in the illicit narcotics trade. Judges often fail to differentiate between users and dealers, leading to inappropriate sentencing. Despite provisions for rehabilitation, many users end up incarcerated due to limited access to treatment facilities and programs. In conclusion, while Law No. 35 of 2009 provides a comprehensive legal framework for addressing drug abuse, its implementation reveals significant shortcomings, particularly concerning sentencing disparities. Judges need comprehensive training to understand the nuances of the law and apply it fairly, considering the roles of different actors in drug-related offenses. Increased investment in rehabilitation programs and facilities is crucial to offer effective treatment options for drug users, reducing recidivism and promoting reintegration into society.